PERSEPSI MASYARAKAT DESA PATONGLOAN KABUPATEN ENREKANG TERHADAP PENGGUNAAN ALAT KONTRASEPSI DALAM PERSPEKTIF HUKUM ISLAM - Islamiyah Rahim; Laela Safriani; Rahman Rasyidin; Muh. Syahrizal (IAI DDI Mangkoso, 2025)
This study discusses the public’s understanding of the use contraceptives from an islamic legal perspective, focusing on the definition and laws of Family Planning. Many people still don’t clearly understand the laws governing Family Planning, especially regarding the difference between the permissible delay of pregnancy and the restriction of offspring which is forbidden in islam. The lack of religious education is one of the main causes of this misunderstanding, so that some people consider Family Planning to be completely forbidden in islam. This study emphasizes the importance of the role ustadz, ulama, and related institutions in conducting intensive and comprehensive counseling.